IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH PADA PENDIDIKAN MENENGAH - Hadi Siswanto (Universitas Islam Balitar, 2014)
This paper describes essentials of school based management and its implementation. Theories concerning effective school and leadership are described. To promote quality of education primarily in the secondary school in Indonesia, four problems have been identified: complex organization system at school level, centralized school management, rigid financial system, and ineffective management. Problems on this matter have been the focus of implementation of school based management in Indonesia promoting quality of all aspects of education